2015
DOI: 10.1371/journal.pone.0133219
|View full text |Cite|
|
Sign up to set email alerts
|

Decoupling of the PI3K Pathway via Mutation Necessitates Combinatorial Treatment in HER2+ Breast Cancer

Abstract: We report here on experimental and theoretical efforts to determine how best to combine drugs that inhibit HER2 and AKT in HER2+ breast cancers. We accomplished this by measuring cellular and molecular responses to lapatinib and the AKT inhibitors (AKTi) GSK690693 and GSK2141795 in a panel of 22 HER2+ breast cancer cell lines carrying wild type or mutant PIK3CA. We observed that combinations of lapatinib plus AKTi were synergistic in HER2+/PIK3CAmut cell lines but not in HER2+/PIK3CAwt cell lines. We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…A STR profile of 21MT1 is not available from the ATCC. The 21MT1 cells used in this study generated a profile that is highly similar to their counterpart that was studied and reported in prior studies in that there is a 15/16 match (94%) with the only difference being loss of an allele in our 21MT1 cell . The HER‐2 amplification status in 21MT1 and JIMT1 cells used in this study has been independently verified by fluorescence in situ hybridization (not shown).…”
Section: Methodssupporting
confidence: 72%
“…A STR profile of 21MT1 is not available from the ATCC. The 21MT1 cells used in this study generated a profile that is highly similar to their counterpart that was studied and reported in prior studies in that there is a 15/16 match (94%) with the only difference being loss of an allele in our 21MT1 cell . The HER‐2 amplification status in 21MT1 and JIMT1 cells used in this study has been independently verified by fluorescence in situ hybridization (not shown).…”
Section: Methodssupporting
confidence: 72%
“…For example, ten patients with PIK3CA -wild type (WT) carcinoma each had PIK3CA exon-20 mutated proliferative lesions present in the same breast tissue specimen [11]. Activating PIK3CA mutations have been shown to evoke downstream PI3K network signaling that fuels cellular transformation and cancer growth in vitro , but their in vivo activity within lesional tissue is more difficult to establish[14, 15], in light of intra-network inhibitory feedback loops or inter-network cross-talk[24, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…The links for which the posterior is shown in E are highlighted in red. (D) Data and posterior predictive for three of the epitopes used for the inference; the data is the 1-hr time point of the dataset of Korkola et al [42]. The previous two datasets are included in the inference as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the data we generated here, we included a part of the dataset provided by Korkola et al [42] in the inference. They performed RPPA measurements of 15 breast cancer cell lines, treated with either lapatinib (250 nM), GSK690693 (250 nM), a combination of the two, or a DMSO control, at 8 time points from 30 minutes to 72 hours.…”
Section: External Datamentioning
confidence: 99%
See 1 more Smart Citation